Robust GPS Satellite Signal Acquisition Using Lifting Wavelet Transform - Djebouri, Djamel; Djebbari, Ali; Djebbouri, Mohamed (Radioengineering Society, 2006)
A novel GPS satellite signal acquisition scheme that utilizes lifting wavelet to improve acquisition performance is proposed. Acquisition in GPS system is used to calculate the code phase (or shift) and find the pseudo-range, which is used to calculate the position. The performance of a GPS receiver is assessed by its ability to precisely measure the pseudo-range, which depends on noise linked to the signals in the receiver’s tracking loops. The level of GPS receiving equipment system noise determines in part how precisely pseudo-range can be measured. Our objective, in this paper, is to achieve robust real-time positioning with maximum of accuracy in the presence of noise. Robust positioning describes a positioning system\'s ability to maintain position data continuity and accuracy through most or all anticipated operational conditions. In order to carry out a robust less complex GPS signals acquisition system and to facilitate its implementation, a substitute algorithm for calculating the convolution by using lifting wavelet decomposition is proposed. Simulation is used for verifying the performance which shows that the proposed scheme based lifting wavelet transform outperforms both FFT search and signal decimation schemes in the presence of a hostile environment.
Keywords: GPS; acquisition; convolution; FFT; decimation; lifting wavelet